Conformational Dynamics of Sensory Rhodopsin II in Nanolipoprotein and Styrene–Maleic Acid Lipid Particles. (29th March 2019) - Mosslehy, Wageiha; Voskoboynikova, Natalia; Colbasevici, Alexandr; Ricke, Adrian; Klose, Daniel; Klare, Johann P.; Mulkidjanian, Armen Y.; Steinhoff, Heinz‐Jürgen
Abstract: Styrene–maleic acid lipid particles (SMALPs) provide stable water‐soluble nanocontainers for lipid‐encased membrane proteins. Possible effects of the SMA‐stabilized lipid environment on the interaction dynamics between functionally coupled membrane proteins remain to be elucidated. The photoreceptor sensory rhodopsin II, Np SRII and its cognate transducer, Np HtrII, of Natronomonas pharaonis form a transmembrane complex, Np SRII2 / Np HtrII2 that plays a key role in negative phototaxis and provides a unique model system to study the light‐induced transfer of a conformational signal between two integral membrane proteins. Photon absorption induces transient structural changes in Np SRII comprising an outward movement of helix F that cause further conformational alterations in Np HtrII. We applied site‐directed spin labeling and time‐resolved optical and EPR spectroscopy to compare the conformational dynamics of Np SRII2 / Np HtrII2 reconstituted in SMALPs with that of nanolipoprotein particle and liposome preparations. Np SRII and Np SRII2 / Np HtrII2 show similar photocycles in liposomes and nanolipoprotein particles. An accelerated decay of the M photointermediate found for SMALPs can be explained by a high local proton concentration provided by the carboxylic groups of the SMA polymer. Light‐induced large‐scale conformational changes of Np SRII2 / Np HtrII2 observed in liposomes and nanolipoprotein particles are affected in SMALPs, indicating restrictions of the protein's conformational freedom. Abstract : The archeal receptor/transducer complex Np SRII/ Np HtrII reveals light‐induced conformational dynamics upon reconstitution into styrene–maleic acid lipid particles.